Extracellular idiotypic immunoglobulin arising from human leukemic B lymphocytes (The Rockefeller University Press, 1980)
The peripheral blood lymphocytes of nine out of nine patients with typical surface Ig-positive chronic lymphocytic leukemia but no paraprotein visible on serum electrophoresis have been shown by radioimmunoassay to export small amounts of pentameric IgM during culture (in the range of 2.4-7.2 ng/10(7) cells per h); three out of nine also exported monomeric IgD (0.7-1.4 ng/10(7) cells per h). Immunoglobulin turned over on the cell surface did not appear to contribute to material in the culture fluid, except possibly as vesicle- bound Ig. In three cases, which included two of the IgD producers, anti- idiotypic antibody raised against the cell surface Fab mu was used to demonstrate the idiotypic nature of the exported Ig. Anti-idiotypic antibody was also used to measure levels of idiotypic Ig in the sera of these three patients as a proportion of the total Ig. Total serum IgM was depressed in all three patients, and the idiotypic IgM represented 43%, 65%, and 96% of the IgM. The findings suggest that in typical chronic lymphocytic leukemia involving B lymphocytes, the export of a small amount of idiotypic Ig by the neoplastic cells in a common or even usual occurrence.